Corn Cost-Return Budget in South Central Kansas - Dumler, Troy J.; Thompson, Curtis R. (My University, 2006)
This publication provides estimated cost and returns for forward farm planning for corn in south central Kansas.
MF2157_2006_10
Keywords: MF2157; Crops; Economics; MF